Measurement of Vcb from the decay process B̄0 → D*+ℓ-v̄ - Abreu, P; Adam, W; Adye, T; Adzic, P; Albrecht, Z; Alderweireld, T; Alekseev, G; Alemany, R; Allmendinger, T; Allport, P; Almehed, S; Amaldi, U; et al. (2001)
A new precise measurement of |Vcb| and of the branching ratio BR(B̄0 → D*+ℓ-v̄ℓ) has been performed using a sample of about 5000 semileptonic decays B̄0 → D*+ℓ-v̄ℓ, selected by the DELPHI detector at LEP I by tagging the soft pion from D*+ → D0π+. The results are: Vcb = (39.0 ± 1.5 (stat.)-2.6+2.5 (syst. exp.) ± 1.3 (syst. th.)) × 10-3, BR(B̄0 → D*+ℓ-v̄ℓ) = (4.70 ± 0.13 (stat.)-0.31+0.36 (syst. exp.))%. The analytic dependencies of the differential cross-section and of the Isgur-Wise form factor as functions of the variable w = vB0 · vD* have also been obtained by unfolding the experimental resolution. © 2001 Published by Elsevier Science B.V.